2019
DOI: 10.5811/westjem.2018.11.40930
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Intravenous Catheter Size and Location for Computed Tomography Pulmonary Angiography

Abstract: Introduction Computed tomography pulmonary angiography (CTPA) is the test of choice for diagnosis of pulmonary embolism (PE) in the emergency department (ED), but this test may be indeterminate for technical reasons such as inadequate contrast filling of the pulmonary arteries. Many hospitals have requirements for intravenous (IV) catheter size or location for CTPA studies to reduce the chances of inadequate filling, but there is a lack of clinical data to support these requirements. The objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…There were higher rates of inadequate contrast enhancement when IV cannulas were positioned in the hand (28.6%), compared to 21.6% in the antecubital fossa and 15.9% in the forearm; however, this small difference was not significant (p = 0.65). This is comparable to findings by Marshall et al 12 (with a larger sample size of 1500) and Roggenland et al 13 These two studies also found no significant difference between different IV cannula sizes, although, similar to our audit, they also had a limited frequency of 22 G IV cannulas. The RCR and American College of Radiology recommends a 20 G or a bigger IV cannula in the antecubital fossa or forearm, but there is no other literature supporting this practice for CTPAs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There were higher rates of inadequate contrast enhancement when IV cannulas were positioned in the hand (28.6%), compared to 21.6% in the antecubital fossa and 15.9% in the forearm; however, this small difference was not significant (p = 0.65). This is comparable to findings by Marshall et al 12 (with a larger sample size of 1500) and Roggenland et al 13 These two studies also found no significant difference between different IV cannula sizes, although, similar to our audit, they also had a limited frequency of 22 G IV cannulas. The RCR and American College of Radiology recommends a 20 G or a bigger IV cannula in the antecubital fossa or forearm, but there is no other literature supporting this practice for CTPAs.…”
Section: Discussionsupporting
confidence: 92%
“…The RCR and American College of Radiology recommends a 20 G or a bigger IV cannula in the antecubital fossa or forearm, but there is no other literature supporting this practice for CTPAs. 7,12,14 They also do not stipulate recommendations for contrast volume. Contrast opacification is related to iodine flow rate, which is a function of iodine concentration and flow rate.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the rate of exams with insufficient enhancement was 7.87%. This result is lower than those of Basson et al 16 and Marshall et al 42 , which found 20.8% and 11.2%, respectively. This result is encouraging.…”
Section: Discussioncontrasting
confidence: 70%
“…A peripheral IV catheter, 20 gauge or larger, placed in the antecubital fossa or forearm is recommended for contrast computed tomography (CT), because a flow rate of 3 mL/s or higher is necessary for injecting contrast media [17]. Contrast CT scans are widely used during ED management [18][19][20]; thus, a 20-gauge or larger IV catheter is usually preferred in EDs.…”
Section: Discussionmentioning
confidence: 99%